Shaking-Table Tests for Immersed Tunnels at Different Sites - Xinjun Cheng; Liping Jing; Jie Cui; Yongqiang Li; Rui Dong (Shock and Vibration, 2017)
Immersed tunnels are typically built in areas subjected to ground motion. Therefore, an evaluation of the seismic performance of the soil-tunnel system is essential. A series of shaking-table tests was conducted to study the influences of the site soil and overlying water layer on the seismic responses of soil deposits and an immersed tunnel. Detailed information on the experiment setup is provided with special focus on the similitude relationship, fabrication of the model system, measurement setup, and loading procedures for a simulation of the seismic waves. Three groups of tests at different sites in dry sand, saturated sand, and saturated sand with an overlying water layer were carried out using the same seismic excitations. The seismic responses of the soil deposits and the dynamic responses of the tunnel model were obtained. The experiment results indicate that, when considering only horizontal earthquake excitations, soil liquefaction significantly influences the propagation of seismic waves and the dynamic responses of the tunnel, whereas the water layer has no obvious effects on the dynamic performance of the ground or tunnel. Furthermore, the acceleration responses of the tunnel elements were analyzed qualitatively, and the joints are deemed important elements in an antiseismic immersed tunnel design.